Ion beam induced secondary electron tomography of acrylonitrile-styrene-acrylate/polycarbonate polymer blends for fused filament fabrication and injection moulding - J. Hernández-Saz; D. Moreno-Sanchez; L. M. Valencia; Y. Gómez; S. I. Molina; M. Herrera (Scientific Reports)
Abstract Polymer blending is an interesting strategy to broaden the combination of properties available for a variety of applications. To understand the behaviour of the new materials obtained as well as the influence of the fabrication parameters used, methods to analyse the distribution of polymers in the blend with resolution below the micrometer are required. In this work, we demonstrate the capability of focused ion beam (FIB) tomography to provide 3D information of the polymer distribution in objects obtained by blending acrylonitrile-styrene-acrylate (ASA) with polycarbonate (PC) (50 wt%), fabricated by Fused Filament Fabrication (FFF) and by Injection Moulding (IM). For this, ion beam induced secondary electron (iSE) images show the capability to distinguish unequivocally the two phases in the blend, providing enough contrasts to perform the 3D experiment. Additionally, Monte Carlo simulations show that the lateral spread for incident electrons in PC is 61.7 nm and for Ga+ ions of 26.2 nm, evidencing a better spatial resolution in iSE imaging. The sputtering rate under the ion beam has been quantified for both neat ASA and neat PC to find optimal parameters for the iSE tomography, resulting in a current of 0.05 nA and a dwell time of 3 µs. Our results reveal significant differences in the morphology of ASA/PC blends depending on the fabrication method. Blends obtained by FFF exhibit strong directionality and a co-continuous morphology, whereas IM objects present a droplet-matrix structure. Also, the interface area between the ASA and PC is quantified to be of 3200 μm² for the FFF sample and 1400 μm² for the IM sample, approximately double in FFF than in IM. The reasons for the different morphologies obtained in the studied blends and possible effects in their mechanical properties are discussed.